Electrochemical Behavior and Determination of Glycyrrhizic Acid at Glassy Carbon Electrode Modified with Graphene - Shi, Gao-Feng; Su, Jin-Mei; Wang, Guo-Ying; Liu, Hai-Xiao; Miao, Jian; Shi, Zhe-Ru (Asian Journal of Chemistry, 2015)
A simple and rapid electrochemical method is developed for the determination of glycyrrhizic acid, based on the excellent properties of graphene. The graphene-modified glassy carbon electrode constructed and the electrochemical behaviour of glycyrrhizic acid at the electrode is investigated in detail. In 0.2 mol/L pH 7 phosphate buffer solution, the redox peak currents of glycyrrhizic acid increased significantly at graphene modified glassy carbon electrode compared with bare glassy carbon electrode, indicating that graphene possessed electrocatalytic activity towards glycyrrhizic acid. The experimental conditions were optimized and the kinetic parameters were investigated. Under the optimal experimental conditions, the oxidation peak current was proportional to glycyrrhizic acid concentration in the range from 3.12 × 10-8 to 1 × 10-6 mol/L with the correlation coefficient of 0.9915. The detection limit was 2 × 10-8 mol/L. Using the proposed method, glycyrrhizic acid was successfully determined in water samples, suggesting that this method can be applied to determine glycyrrhizic acid in different liquorices.